The Etiology of Male Urethral Discharge in Zimbabwe: Results from the Zimbabwe STI Etiology Study. Issue 1 (January 2018) - Rietmeijer, Cornelis A.; Mungati, More; Machiha, Anna; Mugurungi, Owen; Kupara, Vitalis; Rodgers, Luanne; Kilmarx, Peter H.; Roloff, Amy Herman; Gonese, Elizabeth; Tippett-Barr, Beth A.; Shambira, Gerald; Lewis, David A.; et al.
Abstract : Introduction: Sexually transmitted infections (STIs) are managed syndromically in most developing countries. In Zimbabwe, men presenting with urethral discharge are treated with a single intramuscular dose of kanamycin or ceftriaxone in combination with a week's course of oral doxycycline. This study was designed to assess the current etiology of urethral discharge and other STIs to inform current syndromic management regimens. Methods: We conducted a study among 200 men with urethral discharge presenting at 6 regionally diverse STI clinics in Zimbabwe. Urethral specimens were tested by multiplex polymerase chain reaction testing for Neisseria gonorrhoeae, Chlamydia trachomatis, Mycoplasma genitalium, and Trichomonas vaginalis . In addition, serologic testing for syphilis and HIV was performed. Results: Among the 200 studied men, one or more pathogens were identified in 163 (81.5%) men, including N. gonorrhoeae in 147 (73.5%), C. trachomatis in 45 (22.5%), T. vaginalis in 8 (4.0%), and M. genitalium in 7 (3.5%). Among all men, 121 (60%) had a single infection, 40 (20%) had dual infections, and 2 (1%) had 3 infections. Among the 45 men with C. trachomatis, 36 (80%) were coinfected with N. gonorrhoeae. Overall, 156 (78%) men had either N. gonorrhoeae or C. trachomatis identified. Of 151 men who consented to HIV testing, 43 (28.5%) tested positive. There were no differences in HIV status by study site or by urethral pathogen detected. Conclusions: Among men presenting at Zimbabwe STI clinics with urethral discharge, N. gonorrhoeae and C. trachomatis are the most commonly associated pathogens. Current syndromic management guidelines seem to be adequate for the treatment for symptomatic men, but future guidelines must be informed by ongoing monitoring of gonococcal resistance. Abstract : Neisseria gonorrhoeae was the most common pathogen detected among 200 men presenting with urethral discharge recruited from a geographically diverse group of Zimbabwe sexually transmitted infection clinics.